China's Capital and Productivity Measurement Using Financial Resources - Kui-Wai Li (Yale University, Economic Growth Center, 2003)
This paper constructs China's capital stock, which is used in conjunction with a labor variable to estimate a Cobb-Douglas production function for the Chinese economy. Two panels of data are used one for capital formation and one for sources of investment finance. Both national and provincial data are used for these two panels, thus giving a total of four capital-stock series. The Cobb-Douglas estimates show that China's total factor productivity was about 3.4 percent in the post-reform years. Productivity of coastal provinces is higher than inner provinces. Among the various sources of investment finance, foreign direct investment is more efficient than state-funded capital stock.
Keywords: O47; 330; China economic reform; provincial growth and productivity; financial resources; Cobb-Douglas-Produktionsfunktion; Produktivität; Kapitalstock; Anlageinvestition; Räumliche Verteilung; Provinz; China